Racializing heterosexuality: Non-normativity and East Asian characters in James Bond films - Hiramoto, Mie; Pua, Phoebe (Language in Society, 2019)
This article investigates how naturalized models of hegemonic masculinity affect race and sexuality in the James Bond film series. Through close analysis of film dialogue and paralinguistic cues, the article examines how the sexualities of East Asian female and male characters are constructed as oversexed and undersexed, respectively. The analysis therefore affirms Connell's (1995) conception of white heterosexual masculinity as exemplary: East Asian characters are positioned not only as racial Others, but as bodies upon which Bond's heterosexual masculinity is reflected and affirmed as normative and, by extension, ideal. In this way, race is curiously invoked to ‘explain’ sexuality, and Bond's unmarked white masculinity becomes the normative referent for expressions of heterosexual desire. By showing how the sexuality of East Asian characters is typecast as non-normative, the article gestures toward the possibility of theorizing racialized performances of heterosexuality as queer.
Disponible en ligne à https://www-cambridge-org.proxy.bibliotheques.uqam.ca/core/journals/language-in-society/article/racializing-heterosexuality-nonnormativity-and-east-asian-characters-in-james-bond-films/52C50BE7F19552D50389CDED9913BCE3
Keywords: approches et analyses; arts; arts visuels et médiatiques; asie; asie de l'est; cinéma; cours; discipline; identités de genre; intersectionnalité; lin2685; patriarcat; pol5480; premier cycle; privilèges; racisme; ressource en ligne; régions géographiques; systèmes d'oppressions; études de genres

Surrounded: Skeena Reece - Reece, Skeena (Morris and Helen Belkin Art Gallery, 2019)
L'année dernière, la Belkin Art Gallery a eu le plaisir d'acquérir The Time It Takes (2017), l'œuvre d'art pour adultes de Skeena Reece, pour notre collection permanente. À cette époque, Reece a déclaré qu'elle avait toujours voulu travailler avec le berceau pour créer une série de photographies qui documenteraient son emballage de personnes spécifiques dans le sac de mousse. Comme le décrit Reece, "Le sac est un endroit pour se reposer un instant, évoquant un sentiment de nostalgie, pas un sentiment de perte. Être enveloppé donne un sentiment d'apaisement qui suscite de l'espoir pour l'avenir et est un moyen de tenir les gens debout. L'œuvre a commencé comme une performance pour The Fraud That Goes Under the Name of Love, une exposition de groupe à la SFU Audain Gallery de Vancouver en 2016. Elle a ensuite été présentée au Musée d'art contemporain de Montréal pour l'exposition de groupe Piriti: Scène contemporaine autochtone en 2017. La pièce a évolué en une installation pour Oboro, Montréal (2017) et Plug In ICA, Winnipeg (2018) respectivement.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; arts; arts visuels et médiatiques; canada; cours; discipline; exposition; fem3100; performance; premier cycle; périodes historiques; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions